2020
DOI: 10.1515/sjpain-2019-0126
|View full text |Cite
|
Sign up to set email alerts
|

Responses after spinal interventions in a clinical pain practice – a pragmatic observational study

Abstract: IntroductionThere is limited evidence for effect of interventional treatment, and pragmatic studies are needed to assess these interventions within a clinical setting. The aim of this study was to describe patients referred to an interventional pain clinic and investigate responses after spinal intervention in general and for radiofrequency ablation (RFA) and transforaminal epidural corticosteroid administration (TECA), specifically.MethodsThis is a prospective, non-controlled study of patients with chronic sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Particularly, cooled radiofrequency was the most effective. Måwe et al 127 demonstrated, in an observational study, the obvious short-term and long-term improvement of the radiofrequency ablation treated patients. Chen et al 128 demonstrated the effective application of radiofrequency neurotomy on facetogenic chronic LBP via a meta-analysis.…”
Section: Medial Branch Radiofrequency Ablationmentioning
confidence: 96%
“…Particularly, cooled radiofrequency was the most effective. Måwe et al 127 demonstrated, in an observational study, the obvious short-term and long-term improvement of the radiofrequency ablation treated patients. Chen et al 128 demonstrated the effective application of radiofrequency neurotomy on facetogenic chronic LBP via a meta-analysis.…”
Section: Medial Branch Radiofrequency Ablationmentioning
confidence: 96%